2016
DOI: 10.1108/jabs-05-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Modeling volatility on the Karachi Stock Exchange, Pakistan

Abstract: Purpose The current paper aims to fill a gap in the literature by analyzing the nature of volatility on the Karachi Stock Exchange (KSE) 100 index of the KSE, and develop an understanding as to which model is most suitable for measuring volatility among those used. The study contributes significantly to the literature as, compared with the limited previous studies of Pakistan undertaken in the past, it covers three types of data (i.e. daily, weekly and monthly) for the whole period from the introduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Waqar [23] confirmed that both EGARCH and TARCH models were best to capture the leverage (asymmetric) effect of KSE. Furthermore, Akhter and Khan [24] confirmed that daily, weekly and monthly KSE-100 Index return series showed non-normal distribution, stationarity and volatility clustering. They also found that EWMA model was appropriate to measure the volatility level in the monthly series, P-GARCH (1, 1) model in case of daily returns, while the GARCH (1, 1) model for weekly data.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Waqar [23] confirmed that both EGARCH and TARCH models were best to capture the leverage (asymmetric) effect of KSE. Furthermore, Akhter and Khan [24] confirmed that daily, weekly and monthly KSE-100 Index return series showed non-normal distribution, stationarity and volatility clustering. They also found that EWMA model was appropriate to measure the volatility level in the monthly series, P-GARCH (1, 1) model in case of daily returns, while the GARCH (1, 1) model for weekly data.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Javaria and Hassan [34] revealed the nonexistence of herd behaviour in the daily and monthly stock returns of Karachi Stock Exchange. Akhtar and Khan [3] analysed the volatility of KSE-100 index. By using ARCH and GARCH models, the study suggested that weekly, daily and monthly stock returns show volatility, stationarity and nonnormal distribution of KSE returns.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The application of the ARIMA model is supported by Mondal, Shit, and Goswami (2014) that studied the ARIMA model efficiency for various Indian stock sectors and found that the precision of the ARIMA model in the equity prices prediction is exceeding 85%, means that ARIMA model provides sound predictability. Furthermore, the GARCH model is widely used by a large number of researchers for estimating volatility in considering various characteristics of the data (Akhtar & Khan, 2016;Fabozzi, Tunaru, & Wu, 2004). Abdalla (2012) used the GARCH model to analyze the variability in Saudi equity returns and it provides good evidence of the time persistence differing volatility.…”
Section: Modelling Stock Return and Volatilitymentioning
confidence: 99%